Corrigendum to “Measuring implicit attitudes toward physical activity and sedentary behaviors: Test-retest reliability of three scoring algorithms of the Implicit Association Test and Single Category-Implicit Association Test” (Psychol. Sport Exerc. (2017) 31 (70–78) (S1469029216302102) (10.1016/j.psychsport.2017.04.007)) - Chevance, G.; Heraud, N.; Guerrieri, A.; Rebar, Amanda; Boiché, J. (Elsevier BV, 2018)
© 2017 The aim of this correction would be to add a missing information regarding the computation of some scores crucial to the article, and by this way promote the reuse of our findings. There is missing information in the article about the treatment of errors used for both the D-Score and DW-Score. To facilitate proper use of our findings, we would like to more explicitly report the options selected to compute our scores with the open source package IAT.Score provided by Richetin, Costantini, Perugini, & Schönbrodt (2015). For the D-Score, according to the recommendations of Greenwald, Nosek, & Banaji (2003), each error latency was replaced with block mean reaction time + a 600 ms penalty. Moreover a distinction was made between practice and test critical blocks (i.e., score computed separately for practice and test critical trials). For the DW-Score, according to the recommendations of Richetin et al. (2015), error latencies were ignored (i.e., no distinction between correct and error latencies was made). No distinction was made between practice and test critical blocks (i.e., score computed on practice and test critical trials together). Below the options used with the software R (R Development Core Team, 2013) and the package IAT.Score (Richetin et al., 2015) to compute the two scores: D-Score: Parameter 1, option 2 (fixed values trimming); Parameter 2, option 5 (recode); Parameter 3, option 1 (D); Parameter 4, option 2 (distinction). DW-Score: Parameter 1, option 5 (10% winsorizing), Parameter 2, option 1 (ignore); Parameter 3, option 1 (D); Parameter 4, option 1 (no distinction).